MEMPERBAIKI DISTORSI PERSEPSI INTERPERSONAL - Ahmad Sultra Rustan (KOMUNIDA : Media Komunikasi dan Dakwah, 2017)
Perception refers to the process by which we are aware of the stimulus that is about the sensory device and takes place at three stages: the stimulus of the sense device occurs, the stimulus is arranged, the stimulus is interpreted and evaluated. Perception distortion often occurs because the level of sensory accuracy has potential obstacles such as narrow thinking, stereotypes, and lack of cultural sensitivity. Performing perceptions of others is also complicated by the dynamic nature of humans in providing verbal and non-verbal clues. Perception has an influence on the quality of communication, because perception is an evaluation of information received and the basis in the process of establishing messages and relationships. Therefore, the improvement of perception accuracy can be done through (1) improving interpersonal attractiveness (2) communication style implementation in reducing uncertainty, (3) attribution process, (4) performing interpersonal confirmation.